Critical Ischemia Times and the Effect of Novel Preservation Solutions HTK-N and TiProtec on Tissues of a Vascularized Tissue Isograft. Issue 9 (September 2017) - Messner, Franka; Hautz, Theresa; Blumer, Michael J.F.; Bitsche, Mario; Pechriggl, Elisabeth J.; Hermann, Martin; Zelger, Bettina; Zelger, Bernhard; Öfner, Dietmar; Schneeberger, Stefan
Abstract : Background: We herein investigate critical ischemia times and the effect of novel preservation solutions such as new histidine-tryptophan-ketoglutarate (HTK-N) and TiProtec on the individual tissues of a rat limb isograft. Methods: Orthotopic hind-limb transplantations were performed in male Lewis rats after 2 hours, 6 hours, or 10 hours of cold ischemia (CI). Limbs were flushed and stored in HTK-N, TiProtec, HTK, or saline solution. Muscle, nerve, vessel, skin, and bone samples were procured on day 10 for histology, immunohistochemistry, confocal and electron microscopy, and quantitative real-time polymerase chain reaction analysis. Results: Histomorphology of the muscle showed a mainly perivascular inflammatory infiltrate, fibrotic degeneration, and neovascularization after 6 hours and 10 hours of CI. However, centrally aligned nuclei observed in muscle fibers suggest for muscle regeneration in these samples. In addition to Wallerian degeneration, nerve injury was significantly aggravated ( P = 0.032) after prolonged CI. Proinflammatory and regulatory cytokines were most significantly upregulated after 2-hour CI. Our data suggest no superiority of novel perfusates HTK-N and TiProtec in terms of tissue preservation, compared with HTK and saline. Conclusions: Limiting CI time for less than 6 hours is the most significant factor to reduce tissue damage in vascularized tissue transplantation. Signs of muscle regeneration give rise that ischemic muscle damage in limb transplantation might be reversible to a certain extent. Abstract : The authors investigate the impact of ischemia time and the role of preservation solutions on tissue damage in a rat orthotopic hind limb transplantation model. The cold ischemia time is the most significant risk factor for graft dysfunction. Supplemental digital content is available in the text.